Full-color pixel for micro LED display - BANG, UI KYU; BANG, MUN WHAN; RYU SOH YOUNG; RYU YUNG RYEL; RYU RICHARD; BANG, CHAN KYO; KWON, HEE JA (2025)
본 발명은 마이크로 LED 디스플레이용 풀칼라 픽셀에 있어서, 공통 n전극을 공유하면서, 적어도 하나 이상의 적색광 마이크로 LED, 적어도 하나 이상의 녹색광 마이크로 LED 및 적어도 하나 이상의 청색광 마이크로 LED를 포함하는 것을 특징으로 하는 마이크로 LED 디스플레이용 풀칼라 픽셀을 기술적 요지로 한다. The subject matter of the present invention is a full color pixel for a micro LED display, wherein the full color pixel comprises at least one red light micro LED, at least one green light micro LED, and at least one blue light micro LED, which share a common n-electrode of the pixel.